ANALISIS PENGARUH FRAUD DIAMOND DAN GOOD CORPORATE GOVERNANCE DALAM MENDETEKSI KEMUNGKINAN TERJADINYA FRAUDULENT FINANCIAL STATEMENT - Sugi Suhartono (Jurnal Bina Akuntansi, 2020)
In the financial statements there is a possibility of misstatements in the presentation of company’s financial statements relating to errors or fraud made or caused by managers in the company. Misrepresentation in financial statements causes a decrease in the level of trust of users of financial statements and can harm stakeholders. The theories underlying this research include agency theory, fraud diamond, and good corporate governance. The research sample consisted of 46 manufacturing companies listed on the Stock Exchange in the period 2015-2017. Sampling is done by purposive sampling method. Hypothesis testing uses analysis of descriptive statistics, pooling test, independent sample t-test and logistic regression analysis. The results of this study indicate that financial stability, nature of industry, rationalization, and capability have a positive effect on the possibility of fraudulent financial statements. Whereas female on board has a negative effect on the possibility of fraudulent financial statements. But external pressure, personal financial need, effective monitoring and independent board of commissioners are not proven to have effect on the possibility of fraudulent financial statements.